2001
DOI: 10.1021/ma001267l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bis(2-hydroxypropyl)amide-Based Hyperbranched Polyesteramides

Abstract: Polycondensation of 1,2-cyclohexane dicarboxylic anhydride with a calculated molar excess of di-2-propanolamine led to bis(2-hydroxyalkyl)amide based hydroxy-functional hyperbranched polyesteramides in a straightforward manner. Modification reactions of these polymers with lauric esters was conducted in different synthetic approaches. The obtained polymers were characterized by mass spectrometry, using electrospray ionization (ESI) and matrix assisted laser desorption ionization/timeof-flight (MALDI-TOF) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 34 publications
2
66
0
1
Order By: Relevance
“…Random statistical procedures are commonly used to study the structure of hyperbranched polymers, but a series of deviations from the ideal situation are expected due to subsitution effects during polymerization, the occurrence of side reactions and intramolecular cyclization [18][19][20][21][22][23][24][25]. The high mass-average molecular weight and polymer dispersity of the resulting polymes can be controlled by means of the addition of small core molecules [18,19,26], a feature that can be easily incorporated into statistical models.…”
Section: Introductionmentioning
confidence: 99%
“…Random statistical procedures are commonly used to study the structure of hyperbranched polymers, but a series of deviations from the ideal situation are expected due to subsitution effects during polymerization, the occurrence of side reactions and intramolecular cyclization [18][19][20][21][22][23][24][25]. The high mass-average molecular weight and polymer dispersity of the resulting polymes can be controlled by means of the addition of small core molecules [18,19,26], a feature that can be easily incorporated into statistical models.…”
Section: Introductionmentioning
confidence: 99%
“…The method was described by Froeling [21] who and his group synthesized series of hyperbranched polyester amides using different acid anhydrides as A 2 monomers and diisopropanol amine as B 0 B 2 . It is known that DEA is not the best candidate to be used as B 0 B 2 monomer since the presence of primary OH group leads to gelation through the undesired side product from the reaction of the OH group instead of the amine group.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the application of mathematical models, the results of the analytical work confirmed that the ideas of the chemists indeed gave full control over the structures as described above. We published the work in the form of two extensive articles, 11,12 which unexpectedly also yielded us the annual DSM Publication Award (Fig. 6).…”
Section: Structures and Propertiesmentioning
confidence: 99%